Rodent helminths in fragmented atlantic forest areas in the western region of the state of paraná - Benatti, Danise [UNESP]; Andrietti, Luis Felipe; Cândido Júnior, José Flávio; Vogliotti, Alexandre; Moraes, Marcela Figueirêdo Duarte [UNESP]; Tebaldi, José Hairton [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP] (FapUNIFESP (SciELO), 2021)
Rodents are small mammals that can be parasitized by various helminths. This study aimed to identify and describe the ecological indicators of infection in rodents captured in fragments of the Atlantic Forest in the western region of Paraná State, Brazil. Sixty-eight specimens of five rodent species were collected, necropsied, and inspected in search of helminths. The parasites were stored in 70% ethanol, morphologically identified, and counted for calculation of infection indicators. Fourteen species of helminths and one species of Crustacea were recorded: ten in Akodon montensis, four in Mus musculus, two in Thaptomys nigrita, two in Oligoryzomys nigripes, and one in Euryoryzomys russatus. The registered species of parasites were: Rodentolepis akodontis, Angiostrongylus sp., Protospirura numidica criceticola, Trichuris navonae, Syphacia alata, Syphacia criceti, Syphacia evaginata, Trichofreitasia lenti, Stilestrongylus aculeata, Stilestrongylus eta, Stilestrongylus gracielae, Stilestrongylus franciscanus, Stilestrongylus moreli, Stilestrongylus sp., and Pentastomida gen. sp. A positive correlation between the intensity of infection of T. navonae and T. lenti was observed with the body condition index of the host A. montensis. For all species, this study represents a new register of locality, and for eight of them a new host.
Helmintos de roedores em áreas fragmentadas de mata atlântica na região oeste do estado do paraná
Keywords: Cestoda; Fragmentation of habitat; Nematoda; Rodentia